Oral and public confrontation as guarantee of a democratic constitutional criminal procedure - Thiago Miranda Minagé (Revista Brasileira de Direito Processual Penal)
Understanding the criminal process under the aegis of a Democratic State of Law requires, in addition to a critical re-reading of institutes already consolidated in a specific system model, it is still necessary to abandon them when they have legitimacy. It should be understood that the role to be played by the parties through the contradictory is fundamental and will never be possible without the support of orality and publicity of the acts. In order to control the observance of procedural safeguards, it is necessary to establish the contradictory as true guarantor of procedural guarantees. In order to do so, only the respective guarantees will be effective, when, all and any probative production is developed publicly and orally, through a procedural rite previously established in the law. To this end, the present work begins with an analysis of the inquisitive system and its permanent interference in our current criminal process, proposing an overcoming of the current system, which is the accusatory, in view of its inability to contain inquisitive interference, proposing a new Vision of system as a way of perfecting what was then valid, based on the premise of a change of the unifying principle in order to enhance the oral and publicity of the acts.